2011
DOI: 10.1007/s10238-011-0167-0
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of myricetin on renal functions in streptozotocin-induced diabetes

Abstract: Myricetin is a naturally occurring flavonoid that is known to decrease plasma glucose levels in diabetes; however, its influence on renal functions has not yet been determined. This study investigated the effect of myricetin on structural and functional changes occurring in diabetic nephropathy. Male Albino Wistar rats were divided into three groups: normoglycemic, diabetic and myricetin-treated diabetic. Diabetes was induced by intraperitoneal (ip) injection of streptozotocin (50 mg/kg), and rats having fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 28 publications
3
32
0
2
Order By: Relevance
“…Myricetin is another important dietary flavonoid, which occurs mainly in blackcurrants, black grapes, cranberries, bilberries, broad beans, red wine and grape juice (Hertog et al, 1992) but walnuts too are a rich dietary source (Cosmulescu et al, 2010;Cosmulescu & Trandafir, 2011b;Stampar et al, 2006). Myricetin is reported to have beneficial effects on renal functions (Ozcan et al, 2012) or a promising agent for the chemoprevention of skin cancer (Kang et al, 2011). The highest levels of myricetin were recorded in July 15th samples of Valcor leaves (248.99 mg/100 g FW), while the lowest were found in samples taken on June 1st from the Muscelean cultivar (54.14 mg/100 g FW).…”
Section: Resultsmentioning
confidence: 99%
“…Myricetin is another important dietary flavonoid, which occurs mainly in blackcurrants, black grapes, cranberries, bilberries, broad beans, red wine and grape juice (Hertog et al, 1992) but walnuts too are a rich dietary source (Cosmulescu et al, 2010;Cosmulescu & Trandafir, 2011b;Stampar et al, 2006). Myricetin is reported to have beneficial effects on renal functions (Ozcan et al, 2012) or a promising agent for the chemoprevention of skin cancer (Kang et al, 2011). The highest levels of myricetin were recorded in July 15th samples of Valcor leaves (248.99 mg/100 g FW), while the lowest were found in samples taken on June 1st from the Muscelean cultivar (54.14 mg/100 g FW).…”
Section: Resultsmentioning
confidence: 99%
“…Increased oxidative stress and altered antioxidant-protective mechanisms reported in type 1 diabetic animal models [35, 36] can lead to reduced PON1 due to inhibition of the enzyme by its substrates, lipid peroxides [37]. This may provide a mechanism by which decreased PON1 activity promotes atherosclerosis and increased risk for vascular complications in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Myricetin is an important dietary flavonoid, with a potent antioxidant and free-radical scavenging activity. Several studies have demonstrated that myricetin exhibits beneficial effects on bone health (Hsu et al 2007), on renal functions (Ozcan et al 2012) or in the chemoprevention of skin cancer (Kang et al 2011). Extremely high contents of myricetin were found also in walnuts (456.5 mg/100 g FW) by Lugasi et al (2003).…”
Section: Determination Of 17 Phenolic Compounds In Walnut Leaves Extrmentioning
confidence: 97%